2011
DOI: 10.3109/17483107.2011.602173
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technology use is associated with reduced capability poverty: a cross-sectional study in Bangladesh

Abstract: Assistive technology use is associated with reduced capability poverty: a crosssectional study in Bangladesh.Borg, Johan; Östergren, Per-Olof; Larsson, Stig; Rahman, Asm Atiqur; Bari, Nazmul; Khan, Ahm Noman Link to publication Citation for published version (APA): Borg, J., Östergren, P-O., Larsson, S., Rahman, A. A., Bari, N., & Khan, A. N. (2012). Assistive technology use is associated with reduced capability poverty: a cross-sectional study in Bangladesh. Disability and rehabilitation. Assistive technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…The findings provide empirical support for using assistive technology interventions to facilitate full enjoyment of human rights. The results complement a previous report from the same sample, which found that assistive technology use is associated with better opportunities to do things one has reason to value and with better attitudes from neighbours [38]. …”
Section: Discussionsupporting
confidence: 85%
“…The findings provide empirical support for using assistive technology interventions to facilitate full enjoyment of human rights. The results complement a previous report from the same sample, which found that assistive technology use is associated with better opportunities to do things one has reason to value and with better attitudes from neighbours [38]. …”
Section: Discussionsupporting
confidence: 85%
“…The experience of impairment may be a "central and structuring" part of their experience [53,p.238], in which case interventions such as AT do not attempt to "fix" the body, but to address the elements which are "disabling" in a person's situation or environment [54]. Congruent with this idea is the capability approach, where developmental economists [55,56] suggest that disability, like poverty, social exclusion and other forms of disadvantage, be viewed through a "capability lens" and resources allocated to close the capability gap between a person's capacities and their aspirations [56]. Secondly, "disability" is a contested term [57,58] and does not fully represent all AT users: many with long-term illness and people experiencing the impact of agerelated conditions may not identify as disabled, yet benefit from assistive technologies.…”
Section: Assistive Technology Models Involving Peoplementioning
confidence: 99%
“…End poverty in all its forms everywhere Conceptualization: Poverty is both a significant cause and consequence of impairment and disability. Assistive products are powerful enablers for people with impairments to overcome poverty. Target 1.2: By 2030, reduce at least by half the proportion of men, women and children of all ages living in poverty in all its dimensions according to national definitions. Example: A study in Bangladesh found that the use of hearing aids and wheelchairs amongst people with hearing and ambulatory impairments respectively was predictive of reduced poverty (Borg et al, [15]). SDG 2. End hunger, achieve food security and improved nutrition and promote sustainable agriculture Conceptualization: Assistive products enable people with impairments to have the opportunity to contribute to the production of food. Target 2.3: Increase the agricultural productivity and incomes of small-scale food producers, in particular women and family farmers (among others, through non-farm employment). Example: Victims of landmines are often farmers from low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%